Spatio-temporal patterns of Holocene environmental change in southern Sicily - Calò, Camilla; Henne, Paul D.; Curry, Brandon; Magny, Michel; Vescovi, Elisa; La Mantia, Tommaso; Pasta, Salvatore; Vannière, Boris; Tinner, Willy (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Few examples of natural forest remain near the Mediterranean coast. Therefore, it is difﬁcult to study how coastal forests respond to climatic change or their resilience to human impact. We developed new sedimentary record of Holocene vegetation and ﬁre history at Lago Preola, a coastal lake in southwestern Sicily (Italy). In order to verify the existence of forest at large scale on the coast, we compare pollen from Lago Preola, a medium-sized lake (33 ha), to Gorgo Basso, a small lake (3 ha) located nearby with the aim of separating local from extra-local vegetation dynamics through time using pollen percentages and inﬂux. We then compare Lago Preola pollen to the record from Biviere di Gela, a large lagoon (120 ha) situated 160 km to the east in southern Sicily, to examine differences in vegetation dynamics between the two coastal areas during the Holocene. Lake-level reconstructions and ostracode analyses from Lago Preola provide vegetation-independent evidence of climate change, and help to disentangle human and climatic impacts on vegetation. Pollen data indicate Pistacia-dominated shrublands replaced open grasslands in the region surrounding Lago Preola by 9500 cal yr BP. This change coincided with rising lake levels and the development of an ostracode fauna typical of fresh waters. Evergreen forest dominated by Quercus ilex and Olea europaea started to expand by 7000 cal BP and consolidated at 6500 cal yr BP, when lake levels were near their Holocene high. Similarities between pollen from Lago Preola and Gorgo Basso demonstrate that forest was the dominant vegetation type in coastal Sicily during the middle Holocene at both regional and local scales, and even developed in the drier climatic setting around Biviere di Gela. Lake levels fell at Lago Preola after 7000 cal yr BP, with a strong decline accompanied by increasing salinity after 4500 cal yr BP. However, no transition in vegetation matched these inferred hydrological changes. Instead, forests persisted in the surrounding region until 2200 cal BP when human disturbance intensiﬁed. We propose that different climatic factors control lake levels and vegetation in coastal Mediterranean ecosystems. Whereas lake levels are most sensitive to the abundance of winter precipitation, coastal forests depend on spring precipitation and are limited by the length of summer drought. Moisture availability remained suitable for evergreen forests in coastal Sicily during the late Holocene, and humans, not a drier climate drove the regional forest decline.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Holocene; Mediterranean; paleoecology; Paleohydrology; Sicily

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany